TheSGLT-2 inhibitor dapagliflozin ehnanced the anticancer activities and exerts cardioprotective effects during exposure to ipilimumab through NLRP3 inflammasome and pro-fibrotic cytokines. (14th October 2021) - Maurea, N; Quagliariello, V; Bonelli, A; Paccone, A; Conforti, G; Caronna, A; Buccolo, S; Iovine, M; Cerrone, F; Botti, G
Abstract: Background: The clinical trial "DECLARE-TIMI 58" (Dapagliflozin Effect on Cardiovascular Events-Thrombolysis in Myocardial Infarction 58), demonstrated that dapagliflozin, a Sodium glucose cotransporter 2 inhibitor, reduces the composite end point of cardiovascular death/hospitalization for heart failure in a broad population of patients with type 2 diabetes mellitus. Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, achieving unprecedented efficacy in multiple malignancies. However, ICIs are associated with immune-related adverse events involving cardiotoxicity. Purpose: We aimed to study if dapagliflozin could affect ipilimumab-induced anticancer efficacy in human breast cancer cells and reduces its cardiotoxicity. Methods: Co-culture of hPBMCs and human cardiomyocytes or estrogen-responsive and triple-negative breast cancer cells (MCF-7 and MDA-MB-231 cell lines) were exposed to ipilimumab (200 nM) alone or combined to SGLT-2 inhibitor (dapagliflozin) for 72h. After the incubation period, we performed the following tests: determination of cell viability, through analysis of mitochondrial dehydrogenase activity, study of lipid peroxidation (quantifying cellular Malondialdehyde and 4-hydroxynonenal), intracellular Ca2+ homeostasis. Moreover, pro-inflammatory studied were also performed (activation of NLRP3 inflammasome; expression of TLR4/MyD88; transcriptional activation of p65/NF-κB and secretion of cytokines involved in cardiotoxicity (Interleukins 1β, 8, 6). Results: Dapagliflozin increases significantly the cardiomyocytes viability during exposure to Ipilimumab. Indeed, in human breast cancer cells, dapagloflozin showed an opposite behavior with a significant increase in cell mortality and apoptosis (p<0.001 vs only ipilimumab). Cardioprotective properties of dapagliflozin are explainable by the reduction of intracellular Ca2+ overload (−56, 8% vs only ipilimumab; p<0, 001), of the lipid peroxidation (mean reduction of 42, 1–48, 6% compared to cells exposed only to ipilimumab; p<0, 05). Moreover, cells exposed to dapagliflozin during ipilimumab reduced the protein expression of pro-inflammatory cytokines involved in cardiotoxicity and resistance to anticancer effects of ICIs (−47, 2% for Interleukin-1β; −48, 7 for Interleukin 6; −32, 1% for Interleukin 8; p<0, 001 for all vs only ipilimumab groups). Notably, dapagliflozin reduces p65-NF-κB activation (−46, 3 and −49, 3% vs only ipilimumab, p<0.05) and inhibits of 43, 2–53, 7% the expression of NLRP3 inflammasome, p<0.05 for all). No significant effects were seen on TLR4/MYD88 expression in all groups. Conclusion: Dapagliflozin demonstrated cardioprotective properties during Ipilimumab exposure in co-culture model of hPBMCs and cardiomyocytes. Dapagliflozin improves Ca2+ homeostasis and inhibits the pro-inflammatory "NLRP3–NF-κB–cytokines" pathways in cardiac cells. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ricerca corrente grant of Italian Ministry of Health